2021
DOI: 10.3389/feart.2021.668011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Unstable Slope Using Geophysical, UAV, and Geological Techniques: Karakoram Himalaya, Northern Pakistan

Abstract: Given active tectonism, rough terrain, and climate, the mountainous ranges in northern Pakistan are prone to geohazards, including earthquakes, unstable slopes, and landslides. The frequent landsliding in the region poses a risk to communities, economic activities, and transportation networks. In this context, the unstable slope above Mayun village calls for a multi-method approach for better assessment of the slope for planning interventions aimed at hazard mitigation. We conducted an integrated study includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…GPR signal dies out as it interacts with a highly conductive contaminated body, therefore no reflection is observed below the signal attenuation zone [46]. A similar pattern of subsurface contamination generated by dumpsites was also observed by [37,47,48]. In the current study, some diffraction signals are observed towards the agricultural landside, which could be due to uncontaminated land.…”
Section: Waste Characterization and Leachate Plumes Mapping Using Ert And Gpr Imagingsupporting
confidence: 76%
See 2 more Smart Citations
“…GPR signal dies out as it interacts with a highly conductive contaminated body, therefore no reflection is observed below the signal attenuation zone [46]. A similar pattern of subsurface contamination generated by dumpsites was also observed by [37,47,48]. In the current study, some diffraction signals are observed towards the agricultural landside, which could be due to uncontaminated land.…”
Section: Waste Characterization and Leachate Plumes Mapping Using Ert And Gpr Imagingsupporting
confidence: 76%
“…GPR signal dies out as it interacts with a highly conductive contaminated body, therefore no reflection is observed below the signal attenuation zone [46]. A similar pattern of subsurface contamination generated by dumpsites was also observed by [37,47,48].…”
Section: Waste Characterization and Leachate Plumes Mapping Using Ert And Gpr Imagingmentioning
confidence: 58%
See 1 more Smart Citation
“…By analyzing the reflected signal of transmitted waves from the interface where there is a difference in materials, the GPR technique can image shallow subsurface structures (even small cavities) and determine the distance at which they are located. Since the 1980s, GPR has been increasingly accepted for the localization of fractures or cracks [14][15][16][17][18], the identification of stratigraphy or shear deformation [19][20][21][22][23], and the characterization of soil water variations [24][25][26][27] in the geological, environmental, and engineering areas. However, the transmitted waves of GPR are strongly attenuated in conductive zones (e.g., water-rich, clay-rich) and cannot penetrate at greater depths to identify unknown objects of interest.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, integrated regional research or basin-wide studies are required for comprehensive understanding of the fluvial processes and sediment dispersal mechanisms from upstream to downstream GBM concerning Bangladesh. In particular, the advanced remote sensing techniques (such as UAS imagery, LiDAR) for geomorphological research, which are encouragingly used in neighboring countries like China (LeHeron et al 2019), India(Ramsankaran et al 2020;Dhote et al 2022), Bhutan(Dunning et al 2009;Tempa et al 2021), Nepal(Immerzeel et al 2014;Kraaijenbrink et al 2016;Van Woerkom et al 2019), Pakistan(Khan et al 2021), and in other parts of the worlds(Śledź et al 2021), will improve the understandings of landscape evolution and fluvial dynamics not only in the upper Ganges-Brahmaputra but also the entire watershed scale including the downstream reaches in Bangladesh.…”
mentioning
confidence: 99%